Treatment of Sewage by Electrocoagulation and the Effect of High Current Density - Mohd, Nasrullah; Singh, Lakhveer; Zularisam, A. W. (ASSET, 2012)
Treatment of sewage water by electrocoagulation with high cell current densities (605 A/m2, 908 A/m2, 1211 A/m2, 1513 A/m2 and 1816 A/m2) using stainless steel, iron and aluminum electrodes were studied. High current densities applied were very effective for the removal of COD, BOD and SS in 30 minutes. In the electrocoagulation of sewage water, the effect of electrode material, current densities, electrocoagulation time, interelectrode distance and initial pH were examined. The optimum operating range for each operating variable was experimentally determined in order to provide an economical and effective treatment for the sewage water. Therefore, the optimum condition for this treatment is in 30 minutes, by using stainless steel electrode, at 1816 A/m2, in pH7 and 10 mm electrode distances. The optimum treatment condition reduced COD by 98.07%, BOD by 98.07% and SS by 97.64% and the anode loss during the experiment is 9.2 x 102 g.